Mek Mulong: Kedah's Unique Folk Performance (KEMANUSIAAN The Asian Journal of Humanities, 2016)
The essay considers a type of Malay folklore found in the state of Kedah, the mek mulong, which can be categorised as a folk performance. The authentic mek mulong still thrives in Kampung Baru Wang Tepus in Jitra. The essay examines mek mulong as the Kedah Malays' traditional heritage. It analyses the uniqueness of this performance. The essay is based on both Western and local studies on folk performances notably its healing ritual which is not often shown to the public. So far there has been no substantive study on mek mulong while most of the earlier writings on mek mulong are brief, descriptive documentation type of studies. A more in-depth analysis aims to uncover its special features and the uniqueness of this traditional folk performance. In a way the essay is a contribution towards the preservation of folk traditions as without any form of dynamic activism, such folk performances are threatened with extinction.